Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702284
|View full text |Cite
|
Sign up to set email alerts
|

Why and what did we throw out?

Abstract: Issues of consumer food waste in industrialised countries are becoming an increasing concern and this is paralleled by a growing interest in HCI to support more sustainable consumption practices. In this paper we report on a mobile food waste diary application that was made available on app stores, with the aim of enabling motivated people to reflect on their moments of food waste and to explore rationales. Through analysis of the entries submitted by users of the diary application, we identify instances of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 22 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…In contrast, other studies examined users' experiences of food waste, and its connection to other food practices and reasoning behind them [20,22]. For example, Ganglbaeur et al evaluated Foodsharing.de, a community platform that supports food waste reduction by enabling users to collect or offer food items to other users for free [21]. Our work is similar to these studies as we examined domestic food practices through various qualitative methods.…”
Section: Food Hcimentioning
confidence: 94%
“…In contrast, other studies examined users' experiences of food waste, and its connection to other food practices and reasoning behind them [20,22]. For example, Ganglbaeur et al evaluated Foodsharing.de, a community platform that supports food waste reduction by enabling users to collect or offer food items to other users for free [21]. Our work is similar to these studies as we examined domestic food practices through various qualitative methods.…”
Section: Food Hcimentioning
confidence: 94%
“…In addition to considering how to define and categorise reflection, research on reflective experiences has spanned a variety of contexts (see [4] for an overview), including diabetes management [36], social emotional learning [44], monitoring food waste [22], and reflecting within romantic relationships [50]. A growing body of research also concerns itself with the potential of playful interactions (e.g., [23,32]) and games (e.g., [33]) to promote reflection.…”
Section: Related Workmentioning
confidence: 99%
“…Notably, four studies did not explicitly describe the analysis made, but only reported on the results. Study duration ranged from onetime use (Pohl et al, 2017) to 18 months of deployment (Ganglbauer et al, 2015), with most studies spanning a period of three to five weeks. One exception is the study by Bandyopadhyay and Dalvi (2017), which states only that their intervention was deployed during "a limited period of time".…”
Section: Study Selectionmentioning
confidence: 99%
“…Eight studies had 65 individuals or fewer and only 5 studies had 188 or more individuals. Two studies did not report on the sample size; Woolley et al (2016) did not report how many respondents took part in their study, but spoke only in general terms ("a small number of consumers"), and Ganglbauer et al (2015) reported on how many persons downloaded their app, but did not report on the number of persons who actually used it. Design and evaluate an intervention that modifies time perception as a strategy to promote sustainable behaviours Optimise energy use in different stages of cooking food.…”
Section: Study Selectionmentioning
confidence: 99%